Prevalence of maternal HIV infection and knowledge on mother-to-child transmission of HIV and its prevention among antenatal care attendees in a rural area in northwest Cameroon. - Carlson-Babila Sama; Vitalis F Feteh; Maxime Tindong; John T Tanyi; Nestor Mbinkar Bihle; Fru F Angwafo (PLoS ONE, 2017)
BACKGROUND:In 2010, an estimated 141 new HIV infections occurred per day in Cameroon and reports suggest an upsurge of these rates by 2020 if current trends continue. Mother-to-child transmission (MTCT) of HIV is a major public health challenge, and maternal knowledge on HIV transmission during pregnancy and its prevention is important in curtailing paediatric HIV acquisition. OBJECTIVES:We aimed at establishing the prevalence of maternal HIV infection as well as assessing knowledge on HIV, MTCT and prevention of MTCT (PMTCT) of HIV among pregnant women in a rural area of Cameroon. METHODS:This study was conducted in two phases: a 29 month retrospective analysis of 1866 deliveries within three rural health facilities in the Babessi sub-division, Northwest Cameroon and a 1 month prospective phase wherein 150 consenting pregnant women attending antenatal care (ANC) at the study centres were consecutively recruited. RESULTS:Overall, the prevalence of maternal HIV infection was 5.0% (100/2016). All (100%) of the interviewed pregnant women were aware of HIV infection and most (76.7%) had adequate knowledge on its routes of transmission. Meanwhile, only 79.3% (119/150) of them were aware of MTCT with slightly above a third (37.0%) having adequate knowledge on the periods of transmission. The proportions of women correctly stating: during pregnancy, during labour/delivery and during breastfeeding as possible periods of MTCT of HIV were 63.0%, 60.5% and 89.1% respectively. A majority (76.3%) of these women had inadequate knowledge on PMTCT of HIV. CONCLUSION:The overall prevalence of maternal HIV warrants strengthening of current intervention strategies including scaling-up of PMTCT measures. Among others, intensification of HIV-related ANC services to improve the pregnant women's awareness and knowledge on MTCT and its prevention are vital steps in curbing the growing burden of paediatric HIV.